2016
DOI: 10.3892/or.2016.4907
|View full text |Cite
|
Sign up to set email alerts
|

Forkhead-box A1 induces cell senescence in endometrial cancer by regulating p16INK4a

Abstract: Abstract. We previously identified FOXA1 as a tumorsuppressor in EC cells. In the present study, we sought to delineate the different roles of FOXA1 associated with cell senescence and further investigated the correlation between FOXA1 and p16INK4a in the progression of EC. Using reverse transcription-quantitative PCR (RT-qPCR), we found that FOXA1 expression was significantly downregulated in EC cells compared to that in normal endometrial cells. Functionally, senescence-associated β-galactosidase staining, 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
(37 reference statements)
0
3
0
1
Order By: Relevance
“…In our results, the relationship between FOXA1 and aging is contradictory ( Figure 6C , 6D ). Jingyun Wang et al found that FOXA1 could induce endometrial cancer cell senescence by interacting with p16INK4a [ 25 ]. The true relationship between FOXs and senescence in PAAD still needs further experimental validation.…”
Section: Discussionmentioning
confidence: 99%
“…In our results, the relationship between FOXA1 and aging is contradictory ( Figure 6C , 6D ). Jingyun Wang et al found that FOXA1 could induce endometrial cancer cell senescence by interacting with p16INK4a [ 25 ]. The true relationship between FOXs and senescence in PAAD still needs further experimental validation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that FOXA1 is a tumor suppressor in endometrial cancer 7,8, through modulation of the proliferation and migration of endometrial cancer cells 7, and that it has a possible interaction with ER 8. It has been also suggested that FOXA1 promotes cell senescence in endometrial cancer by interaction with p16 13. FOXA1 is overexpressed in ER-positive endometrial cancer cell lines, and in both normal endometrium and well-differentiated endometrial cancer tissues; also, the forced expression of FOXA1 inhibits endometrial cancer cell proliferation, whereas FOXA1 depletion promotes cell viability and is associated with tumorigenesis 8.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that FOXA1 is upregulated in both replicative and oncogene-induced senescent cells [18]. Forced expression of FOXA1 in endometrial cancer cells leads to cellular senescence [24]. Sustained activation of Ras is known to be cause of oncogene-induced senescence [25,26].…”
Section: Discussionmentioning
confidence: 99%